2017
DOI: 10.1017/s2040470017000978
|View full text |Cite
|
Sign up to set email alerts
|

Comparing efficiency of different sampling schemes to estimate yield and quality parameters in fruit orchards

Abstract: Different sampling schemes were tested to estimate yield (kg/tree), fruit firmness (kg) and the refractometric index (°Baumé) in a peach orchard. In contrast to simple random sampling (SRS), the use of auxiliary information (NDVI and apparent electrical conductivity, ECa) allowed sampling points to be stratified according to two or three classes (strata) within the plot. Sampling schemes were compared in terms of accuracy and efficiency. Stratification of samples improved efficiency compared to SRS. However, y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 9 publications
1
8
0
Order By: Relevance
“…One important reason could be the small sized orchards usually have there. Nevertheless, and as pointed out by Käthner and Zude-Sasse (2015) and Arnó et al (2017), even in small orchards there may be differences in soil properties affecting tree growth and fruit quality.…”
Section: Introductionmentioning
confidence: 97%
“…One important reason could be the small sized orchards usually have there. Nevertheless, and as pointed out by Käthner and Zude-Sasse (2015) and Arnó et al (2017), even in small orchards there may be differences in soil properties affecting tree growth and fruit quality.…”
Section: Introductionmentioning
confidence: 97%
“…Field yield estimation is often carried out by sampling. Observations of yield components are then made on a limited number of vines (Carrillo et al, 2016;Arnó et al, 2017;Wolpert and Vilas, 1992) and the mean value is generally used to provide an estimation of the field yield. To have a relevant estimation of the final yield, sampling is often carried out a few days before harvest, at a critical period in terms of workload.…”
Section: Introductionmentioning
confidence: 99%
“…Recent works (Carrillo et al 2016;Uribeetxebarria et al 2019;Arnó et al 2017) have shown the interest of integrating auxiliary data to improve sampling strategies and yield estimation for perennial crops. Among possible auxiliary information, vegetation index derived from multispectral airborne images is of great interest since they permit to characterise the spatial variability of several fields; in one acquisition, with a high spatial resolution (< 1 m) and at an optimal date.…”
Section: Introductionmentioning
confidence: 99%